Imaging-based assessment of muscles and malnutrition predict prognosis in patients with primary hepatocellular carcinoma - Hitomi Takada; Leona Osawa; Yasuyuki Komiyama; Masaru Muraoka; Yuichiro Suzuki; Mitsuaki Sato; Shoji Kobayashi; Takashi Yoshida; Shinichi Takano; Shinya Maekawa; Nobuyuki Enomoto (PLoS ONE, 2025)
Background The significance of imaging-based assessment of muscles and malnutrition in patients with primary hepatocellular carcinoma (HCC) remains unclear. This study aimed to elucidate the prognostic role of the combination of Low Muscle Volume and Value (LMVV) and malnutrition. Methods A total of 714 Child-Pugh grade A/ B patients with first-diagnosed HCC were enrolled, and analyzed factors associated with overall survival. LMVV was defined using psoas muscle mass index and computed tomography values of multifidus muscle at the level of the third lumbar vertebra. We used hypoalbuminemia, Child-Pugh grade B, Subjective Global Assessment (SGA) grade B/C, and Royal Free Hospital Nutrition Prioritizing Tool (RFH-NPT) score > 2 as malnutrition factors in this study. Results At baseline, 29% showed LMVV, and 59% met one or more of the malnutrition criteria. No items meeting the criteria of LMVV and malnutrition was observed in 41%, 1 of them was found in 29%, and both were found in 29%. The number of items meeting criteria was an independent factor for a shorter survival. The frequency of liver-related deaths did not differ by presence of LMVV alone, while it was associated with malnutrition. In contrast, the incidence of other types of deaths was influenced by LMVV and malnutrition. Conclusions The combination of LMVV and malnutrition is a prognostic factor in patients with primary HCC.